2014
DOI: 10.1111/1365-2435.12374
|View full text |Cite
|
Sign up to set email alerts
|

Exotic invasive plants alter thermal regimes: implications for management using a case study of a native ectotherm

Abstract: Summary1. Exotic invasive plants can alter ecosystem structure and function, yet there is a paucity of evidence regarding broadly applicable mechanisms. We hypothesized that denser growth patterns characteristic of exotic invasive plants lead to a common effect of reduction and homogenization of environmental temperatures and that these alterations compromise thermal quality of habitat for ectotherms. 2. We quantified thermal regimes within native and exotic plant-dominated habitats, including monocultures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Copperheads rely on rocky overwintering hibernacula located high on steep‐sided and often south‐facing slopes (Maigret & Cox, ), sites disproportionately destroyed by surface mining (Maigret et al, ). Copperheads are also generally intolerant of dense, invasive vegetation common to many reclaimed surface mines (Carter, Eads, Ravesi, & Kingsbury, ; Carter, Ravesi, Eads, & Kingsbury, ). Additionally, herpetofauna generally, and pit vipers in particular, have been shown to be especially vulnerable to vehicular traffic (Andrews & Gibbons, ; Shepard, Dreslik, Jellen, & Phillips, ), and elevated genetic differentiation associated with highways has been detected using microsatellite markers (Clark, Brown, Stechert, & Zamudio, ; DiLeo, Rouse, Dávila, & Lougheed, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Copperheads rely on rocky overwintering hibernacula located high on steep‐sided and often south‐facing slopes (Maigret & Cox, ), sites disproportionately destroyed by surface mining (Maigret et al, ). Copperheads are also generally intolerant of dense, invasive vegetation common to many reclaimed surface mines (Carter, Eads, Ravesi, & Kingsbury, ; Carter, Ravesi, Eads, & Kingsbury, ). Additionally, herpetofauna generally, and pit vipers in particular, have been shown to be especially vulnerable to vehicular traffic (Andrews & Gibbons, ; Shepard, Dreslik, Jellen, & Phillips, ), and elevated genetic differentiation associated with highways has been detected using microsatellite markers (Clark, Brown, Stechert, & Zamudio, ; DiLeo, Rouse, Dávila, & Lougheed, ).…”
Section: Introductionmentioning
confidence: 99%
“…Copperheads rely on rocky overwintering hibernacula located high on steep-sided and often south-facing slopes (Maigret & Cox, 2018), sites disproportionately destroyed by surface mining . Copperheads are also generally intolerant of dense, invasive vegetation common to many reclaimed surface mines (Carter, Eads, Ravesi, & Kingsbury, 2015;Carter, Ravesi, Eads, & Kingsbury, 2017). Additionally, herpetofauna generally, and pit vipers in particular, have been shown to be especially vulnerable to vehicular traffic (Andrews & Gibbons, 2005;Shepard, Dreslik, Jellen, & Phillips, 2008), and elevated genetic differentiation associated with highways has been detected using microsatellite markers (Clark, Brown, Stechert, & Zamudio, 2010;DiLeo, Rouse, Dávila, & Lougheed, 2013 Using RADseq data and nonspatial and spatially informed analyses, we investigated the potential for recently formed population structure across A. contortrix in eastern Kentucky as a result of this landscape change, with a particular focus on the effects of habitat fragmentation via surface coal mining and through the network of historical (c. 1920) and more recently constructed (c. 1975) high-traffic roads.…”
mentioning
confidence: 99%
“…Changes in thermal quality caused by plant invasions are expected to be largest when the alien plants present novel growth forms or structural features relative to the dominant native vegetation [9,26]. For example, larger size and faster-growing alien trees can cause reductions in light and temperature in shrubland habitats [27,28], and those with extended phenology can lengthen thermal effects beyond the growing season of native vegetation [29].…”
Section: (A) Changes In Thermal Landscapesmentioning
confidence: 99%
“…Using radio-tracking, field observations and experimental trials, several studies in this review showed that invaded areas were actively avoided by individuals, including females selecting incubation sites (e.g. [27,29,45]). The responses of ectothermic individuals using invaded areas were also assessed.…”
Section: (B) Ectothermic Individuals' Responsesmentioning
confidence: 99%
“…We placed 10 physical models of massasaugas throughout the study site to collect hourly operative environmental temperatures (T e ) that approximate T b s of snakes in the absence of clear behavioral or physiological thermoregulation (i.e., thermoconformity) (Blouin-Demers & Weatherhead, 2001;Carter, Eads, Ravesi, & Kingsbury, 2015;Harvey & Weatherhead, 2011). The models were 10-cm-long and 2.54-cm-diameter copper tubes which we painted dark brown to mimic the thermal properties of a massasauga.…”
Section: Thermoregulationmentioning
confidence: 99%